2017
DOI: 10.9744/dimensi.44.2.179-188
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Sitting Preferences at Plaza in Educational Institution

Abstract: The purpose of this research is to understand the relationship between sitting preferences and student activities by taking the case of public plaza at the Central Office of the Faculty of Engineering (KPFT) Universitas Gadjah Mada (UGM) in Yogyakarta. KPFT UGM as research object is divided into five zones, namely Zone A (west), Zone B and C (south), and Zone D and E (north). Field observation was done within one month period during working days (weekday) and weekends with observation time: in the morning (08.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…While several studies conducted in healthcare environments show that factors such as privacy, comfort, seating arrangement, availability of visually appealing furniture, and positive distractions in the waiting area can positively impact users’ perception of care quality, they do not focus on the aspects of seating itself that are important to users during the waiting experience. There is some evidence of impact of seating clusters or arrangement on social interaction in classrooms and plazas in educational institutes (Marcillia & Kesumasari, 2017), and perceived restorativeness in hotel lobbies (Rutkin, 2005). Zhu and Argo (2013) conducted a study on a university campus and found that circular-shaped seating activated the need to belong and respond to family-oriented information and advertisements.…”
mentioning
confidence: 99%
“…While several studies conducted in healthcare environments show that factors such as privacy, comfort, seating arrangement, availability of visually appealing furniture, and positive distractions in the waiting area can positively impact users’ perception of care quality, they do not focus on the aspects of seating itself that are important to users during the waiting experience. There is some evidence of impact of seating clusters or arrangement on social interaction in classrooms and plazas in educational institutes (Marcillia & Kesumasari, 2017), and perceived restorativeness in hotel lobbies (Rutkin, 2005). Zhu and Argo (2013) conducted a study on a university campus and found that circular-shaped seating activated the need to belong and respond to family-oriented information and advertisements.…”
mentioning
confidence: 99%
“…Locational accessibility to support facilities therefore may have increased space preferences of users in common spaces [48,23]. Early attempts that embrace open and flexible office designs include the ability to rearrange tables and seating to support interaction and communication.…”
Section: Common Spaces Within Buildingsmentioning
confidence: 99%
“…Campuses also implemented amenities such as cafeterias and fitness centers to support inter-disciplinary and cross-departmental interaction [30]. On a larger scale, locational accessibility of common spaces to surrounding functions like food courts, fitness centers, copy rooms, offices and so forth play a significant role in space preferences and may illustrate users' considerations of whether the location is accessible and well-placed for the purpose of their activity [48,23,49]. Thus, common spaces become part of a network of support functions that may determine its success, as walking distances [50,24] and the distance to entrances [22] are strongly related to spatial choices.…”
Section: Common Spaces Within Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, learning activities can be divided into two types (Faizati, 2013) in (Marcillia, S. R. & Kesumasari, D., 2017), namely: a) active learning activities that require movements or interactions with one another (e.g., the exhibitions, experiments and discussions, and b) passive learning activities that do not require a lot of movements or interactions with one another (e.g. searching for literature, reading the book, drawing and writing).…”
Section: Introductionmentioning
confidence: 99%